Development and Effectiveness of Interactive Learning Media For Mathematical Logic and Set Towards Students’ Self Confident on Computer. - Fahmi, Syariful; Priwantoro, Soffi Widyanesti; Cahdriyana, Rima Aksen (International Journal of Engineering and Technology, 2018)
This research aims to find out how to develop and produce interactive learning media using Adobe Flash CS3 for students of mathematics education in the course of mathematical logic and Set in class D academic year of 2017/2018, as well as how the quality of the resulting learning media. The population in this research is the entire class D in first semester student in Mathematics Education academic year of 2017/2018. The model used is the development model of Borg and Gall which includes: (1) analysis of the content standards, (2) the collection of references to interactive media, (3) the preparation of draft interactive media, and (4) creation of interactive media in the form of digital discs (CD). Interactive multimedia has produced score of good quality according to the assessment of the learning material experts, media experts, and students of Class D academic year of 2017/2018, with an average score was 209.48 with maximum score of 260. The effectiveness toward students’ confidents on computer shows there, 73.81% of students feel able to get good grades if learning with computers, 57.14% of students feel very confident when starting to learn with computers, and 50% students learn to feel confident with computers.